Technika a kultura w ujęciu Waltera Benjamina w polskich opracowaniach z drugiej połowy XX wieku = Technology versus culture according to Walter Benjamin in Polish studies from the second half of the 20th century - Świt, Mirosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Walter Benjamin - a great observer of contemporary days expressed his views on culture, art, literature, history and philosophy with great ease. He always tried to examine cultural facts as a widely comprehended social integrity. With inherent acuteness, he perceived the relationships between sensual perception and the ongoing historical changes. In his opinion, a man undergoes both historie and social changes and the phenomenon of mass production is a sign of those changes.
Keywords: czasopismo akademickie; polityka; kultura; czasopismo